Iranian Pharmaceutical Industry Opportunities in Iraq - Ahmed Hayder Mohsin Al Iami; Saman Zartab; Mona Jaberidoost; Alireza Yektadoost; Shekoufeh Nikfar; Abbas Kebriaeezadeh (Tehran University of Medical Sciences, 2019)
Background: The socioeconomic and political situation of Iraq has provided a wide and open market. Because of the weak pharmaceutical industry and war, Iraq has a huge demand for pharmaceutical and medical services; this country is a reliable market in the pharmaceuticals trade. Iran has a long border and good political relationship with Iraq, besides a great pharmaceutical industry. However, because of wrong policies and the lack of competition power, Iran failed to significantly impact Iraq's pharmaceutical market. We aimed to analyze Iraq's pharmaceutical trade market, address the factors affecting pharmaceuticals trade between Iran and Iraq, and provide suggestions to promote Iran in Iraq's pharmaceutical market. Methods: Two questionnaires were designed based on the information obtained from articles related to the pharmaceutical industry. Questionnaires were completed by 10 Iraqi pharmaceutical experts. Then, we analyzed the obtained results by Simple Additive Weight (SAW) method. Based on the results of the analysis, we attempted to find the most important factors affecting Iran's role in Iraq pharmaceutical market and clarify its situation. Results: The achieved results revealed 10 factors out of the 45 factors were more important and the majority of them were related to quality and marketing strategy. Conclusion: The study has suggested that quality and marketing power are the most important factors that affect the Iran-Iraq pharmaceutical business.